Penerapan Metode Fonik dalam Meningkatkan Kemampuan Membaca Permulaan di Sekolah Dasar - Dzikra, Salma Mutiara (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
The low initial reading ability of elementary school students in Indonesia is an urgency for education in Indonesia because reading is the initial capital that students must have. The learning methods used by educators also influence learning outcomes. One method that can be used to improve beginning reading skills is the phonics method. This article uses a research method based on Systematic Literature Review (SLR) with the Preferred Reporting Items For Systematic Reviews and Meta Analyses (PRISMA) protocol to search for and analyze articles related to phonics methods in improving beginning reading skills that have been published between 2019 and 2024. Article search carried out using the Google Scholar and Semantic Scholar databases with the help of the